Indium titanium cerium niobium oxide ceramic target material, preparation method and application thereof, and transparent conductive oxide film
By combining indium titanium oxide cerium niobium ceramic targets and microwave sintering technology, the problems of insufficient near-infrared transparency and mobility of traditional indium tin oxide targets have been solved, and high-density, high-strength ceramic targets and high-performance transparent conductive oxide films have been prepared, which are suitable for the photovoltaic industry.
Patent Information
- Application Number
- CN202411799809.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Traditional indium tin oxide (ITO) targets are transparent under visible light but opaque in the near-infrared region. They have low carrier mobility and insufficient density and strength, which makes them prone to cracking during high-power coating processes, thus failing to meet the requirements of heterojunction photovoltaic cells.
An indium-titanium-cerium-niobium oxide ceramic target was prepared by microwave sintering using a combination of indium oxide, titanium oxide, cerium oxide, and niobium oxide. This process controlled grain growth, reduced defects, and improved the target density and strength. A transparent conductive oxide thin film was then prepared by physical vapor deposition sputtering.
A high-density, high-strength indium titanium oxide cerium niobium ceramic target was developed. The resulting transparent conductive oxide film exhibits high carrier mobility and high light transmittance, avoiding cracking issues during the coating process and making the sintering process more efficient.
Smart Images

Figure BDA0005177854550000061 
Figure BDA0005177854550000071 
Figure BDA0005177854550000081
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photovoltaic target technology, specifically relating to an indium titanium oxide cerium niobium ceramic target, its preparation method and application, and a transparent conductive oxide thin film. Background Technology
[0002] With the development of the photovoltaic industry, especially the increasing market share of heterojunction photovoltaic cells, traditional indium tin oxide (ITO) sputtering targets with a mass ratio of 90 / 10 can no longer meet the requirements of heterojunction cells. This is because traditional ITO sputtering targets are only transparent under visible light but opaque in the near-infrared region, and their carrier mobility is only 30–40 cm⁻¹. 2 V -1 S -1 .
[0003] By adding trace amounts of oxides such as tungsten oxide, cerium oxide, or zirconium oxide to indium oxide, transparent conductive oxide targets with high infrared transmittance and high mobility can be obtained. However, adding tungsten oxide, cerium oxide, or zirconium oxide alone can only produce ceramics with a density of 70-80%, and it is impossible to prepare ceramics with a density of over 99%. At the same time, because the density of ceramic targets is low, their strength is also low, making magnetron sputtering coating impossible and large-size sputtering coating impossible.
[0004] Furthermore, to achieve high-quality thin films, photovoltaic ceramic targets typically require high deposition power to create dense, crystalline films. However, ensuring proper deposition at high power necessitates high strength from the ceramic target. Currently, high-mobility ceramic targets generally only have a strength of 130–150 MPa, making them prone to cracking during photovoltaic deposition. Summary of the Invention
[0005] In view of this, the purpose of the present invention is to provide an indium titanium oxide cerium niobium ceramic target, its preparation method and application, and a transparent conductive oxide thin film. The indium titanium oxide cerium niobium ceramic target has high density and high strength, and the transparent conductive oxide thin film prepared therefrom has high carrier mobility, high conductivity and high light transmittance.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] This invention provides an indium titanium cerium niobium ceramic target material, comprising the following components: indium oxide, titanium oxide, cerium oxide, and niobium oxide;
[0008] The mass ratio of indium oxide, titanium oxide, cerium oxide and niobium oxide is 97-99:1-0.3:1-0.3:1-0.2.
[0009] Preferably, the indium titanium oxide cerium niobium ceramic target has a relative density ≥99% and a bending strength ≥190MPa.
[0010] The present invention also provides a method for preparing the indium titanium oxide cerium niobium ceramic target described in the above technical solution, comprising the following steps:
[0011] Indium oxide powder, titanium oxide powder, cerium oxide powder, niobium oxide powder, dispersant, binder, defoamer and water are mixed to form a slurry, which is then ball-milled to obtain the ball-milled slurry.
[0012] The ball-milled slurry is granulated, and the resulting mixed powder is molded to obtain a mixed preform of indium titanium cerium niobium oxide;
[0013] The indium titanium cerium niobium mixed preform is sequentially degreased and sintered to obtain the indium titanium cerium niobium ceramic target.
[0014] Preferably, the sintering temperature is 1100–1200°C, and the holding time is 3–5 hours.
[0015] Preferably, the sintering is microwave sintering; the microwave frequency of the microwave sintering is 2.45 GHz.
[0016] Preferably, the ball milling speed is 1000-2500 rpm; the ball milling time is 1-4 hours.
[0017] Preferably, the molding process is cold isostatic pressing; the pressure of the cold isostatic pressing is 150-300 MPa, and the holding time is 5-30 min.
[0018] The present invention also provides the application of the oxide-doped indium oxide-based target material described in the above technical solution or the oxide-doped indium oxide-based target material prepared by the preparation method described in the above technical solution in the photovoltaic industry.
[0019] The present invention also provides a transparent conductive oxide thin film, which is prepared by sputtering an indium titanium oxide cerium niobium ceramic target.
[0020] The indium titanium cerium niobium ceramic target is the indium titanium cerium niobium ceramic target described in the above technical solution or the indium titanium cerium niobium ceramic target prepared by the preparation method described in the above technical solution.
[0021] Preferably, the sputtering coating is a physical vapor deposition sputtering coating; the power of the sputtering coating is 120-200W.
[0022] This invention provides an indium titanium oxide (ITO) cerium niobium ceramic target, comprising the following components: indium oxide, titanium oxide, cerium oxide, and niobium oxide; the mass ratio of ITO, titanium oxide, cerium oxide, and niobium oxide is 97-99:1-0.3:1-0.3:1-0.2. In this invention, titanium oxide can suppress abnormal grain growth, refine grains, and inhibit defect formation, thereby improving the target strength. The ionic radius of cerium is close to that of indium ions, resulting in smaller lattice deformation when doped with cerium. Furthermore, cerium oxide can reduce the oxygen vacancy content, thereby reducing carrier concentration and increasing mobility. High mobility reduces long-wavelength absorption, thus improving transmittance. Therefore, the ITO cerium niobium ceramic target provided by this invention has high density, high purity, and high strength, and will not crack during photovoltaic coating. The transparent conductive oxide thin film prepared using it has high carrier mobility, high conductivity, and high transmittance. Moreover, the ITO cerium niobium ceramic target provided by this invention exhibits no expansion, deformation, or cracking during sintering.
[0023] The present invention also provides a method for preparing the indium titanium oxide cerium niobium ceramic target. During the sintering process, niobium oxide can form a liquid phase that surrounds the indium oxide grain boundaries, greatly promoting particle rearrangement and mass transfer, thereby promoting sintering and reducing the temperature required for sintering.
[0024] Furthermore, the present invention introduces microwave sintering, which can reduce the sintering temperature and sinter some products that cannot be sintered at high temperatures into a dense state, thereby achieving high density. While achieving high density, the strength is naturally improved. Moreover, microwave sintering can also significantly shorten the sintering time of large-size ceramic targets. Detailed Implementation
[0025] This invention provides an indium titanium oxide cerium niobium ceramic target, comprising the following components:
[0026] Indium oxide, titanium oxide, cerium oxide, and niobium oxide;
[0027] The mass ratio of indium oxide, titanium oxide, cerium oxide and niobium oxide is 97-99:1-0.3:1-0.3:1-0.2.
[0028] Unless otherwise specified, the present invention does not have special requirements on the source of raw materials used, and commercially available products well known to those skilled in the art can be used.
[0029] The indium titanium oxide cerium niobium ceramic target provided by the present invention comprises the following components: indium oxide (In2O3), titanium oxide (TiO2), cerium oxide (CeO2) and niobium oxide (Nb2O5); the mass ratio of indium oxide, titanium oxide, cerium oxide and niobium oxide is 97-99:1-0.3:1-0.3:1-0.2.
[0030] In one embodiment, the mass ratio of indium oxide, titanium oxide, cerium oxide, and niobium oxide is 97-98:0.9-0.4:0.9-0.4:0.9-0.2, and in specific embodiments, it is 97.3:0.9:0.9:0.9, 97.7:0.9:0.9:0.5, 98.1:0.9:0.5:0.5, 98.5:0.5:0.5:0.5, or 99:0.4:0.4:0.2.
[0031] In one embodiment, the density of the indium titanium oxide cerium niobium ceramic target is 7.095–7.112 g / m³. 3 The relative density is ≥99%, specifically 99.23-99.46% in the embodiments; the flexural strength is ≥190MPa, specifically 192-238MPa in the embodiments.
[0032] This invention also provides a method for preparing the indium titanium oxide cerium niobium ceramic target according to the above technical solution, comprising the following steps:
[0033] Indium oxide powder, titanium oxide powder, cerium oxide powder, niobium oxide powder, dispersant, binder, defoamer and water are mixed to form a slurry, which is then ball-milled to obtain the ball-milled slurry.
[0034] The ball-milled slurry is granulated, and the resulting mixed powder is molded to obtain a mixed preform of indium titanium cerium niobium oxide;
[0035] The indium titanium cerium niobium mixed preform is sequentially degreased and sintered to obtain the indium titanium cerium niobium ceramic target.
[0036] This invention involves mixing indium oxide powder, titanium oxide powder, cerium oxide powder, niobium oxide powder, dispersant, binder, defoamer, and water to form a slurry, which is then ball-milled to obtain a ball-milled slurry.
[0037] In one embodiment, the dispersant is triethanolamine; the mass of the dispersant is 0.5-1.5% of the total mass of indium oxide, titanium oxide, cerium oxide and niobium oxide, and in a specific embodiment it is 0.5-1%.
[0038] In one embodiment, the adhesive is one or more of polyvinyl alcohol (PVA), carboxymethyl cellulose, polyacrylamide, and polyacrylate, with polyvinyl alcohol (PVA) being a specific example; the mass of the adhesive is 1 to 2% of the total mass of indium oxide, titanium oxide, cerium oxide, and niobium oxide, with 1.5 to 2% being a specific example.
[0039] In this invention, the dispersant enables the raw material powder to be uniformly dispersed in water during the preparation of the slurry, and the binder gives the mixed slurry a certain viscosity, which is beneficial for subsequent molding.
[0040] In one embodiment, the defoamer is polyoxypropylene glycerol ether; the mass of the defoamer is 0.05 to 0.3% of the total mass of indium oxide, titanium oxide, cerium oxide and niobium oxide, and in a specific embodiment it is 0.1 to 0.2%.
[0041] In one embodiment, the water is deionized water; the mass of the water is 35-45% of the total mass of indium oxide, titanium oxide, cerium oxide and niobium oxide, and in a specific embodiment it is 36-40%.
[0042] In one embodiment, the ball milling equipment is a sand mill; the ball milling media is zirconia beads; the particle size of the zirconia beads is 0.2–0.6 mm, specifically 0.3–0.5 mm in this embodiment; the ball milling speed is 1000–2500 rpm, specifically 1500–2400 rpm in this embodiment; the ball milling time is 1–4 hours, specifically 1.5–3 hours in this embodiment; and the particle size of the solid material in the slurry after ball milling is D. 50 <0.3μm, D 90 <0.8μm, specifically D in the embodiment 50 ≤0.2μm, D 90 ≤0.5μm.
[0043] After obtaining the ball-milled slurry, the present invention granulates the ball-milled slurry and shapes the resulting mixed powder to obtain a mixed preform of indium titanium cerium niobium oxide.
[0044] In one embodiment, the granulation is spray drying granulation; the spray drying granulation temperature is 220-245℃, and in a specific embodiment it is 225-235℃.
[0045] As one implementation method, after granulation, the method further includes: sieving the granules obtained from granulation; the sieving is performed using a 60-100 mesh sieve, specifically 60-80 mesh in this embodiment.
[0046] In one embodiment, the molding is cold isostatic pressing; the pressure of the cold isostatic pressing is 150-300 MPa, specifically 200-280 MPa, and the holding time is 5-30 min, specifically 10-20 min.
[0047] After obtaining the indium titanium cerium niobium mixed green body, the present invention degreases and sinters the indium titanium cerium niobium mixed green body sequentially to obtain the indium titanium cerium niobium ceramic target material.
[0048] In one embodiment, the degreasing temperature is 600–800°C, specifically 700–800°C, and the holding time is 2–3 hours, specifically 2–2.5 hours; the heating rate to the degreasing temperature is 1–1.5°C / min, specifically 1.2–1.5°C / min; the degreasing is carried out in air; the degreasing is microwave degreasing; and the microwave frequency for microwave degreasing is 2.45 GHz.
[0049] In one embodiment, the sintering temperature is 1100–1200℃, specifically 1150–1200℃, and the holding time is 3–5 hours, specifically 4–5 hours; the heating rate to the sintering temperature is 1–1.5℃ / min, specifically 1.2–1.5℃ / min; the sintering is microwave sintering; the microwave frequency of the microwave sintering is 2.45 GHz; oxygen is introduced during the sintering process; the oxygen pressure during the sintering process is 0.05–0.1 MPa, specifically 0.07–0.1 MPa.
[0050] The microwave sintering method used in this invention densifies the pressed indium titanium cerium niobium mixed blank by converting microwave energy into heat energy.
[0051] This invention increases the oxygen partial pressure in the sintering environment, which can suppress the decomposition of oxide raw materials at high temperatures, thereby increasing the density of the target material.
[0052] The present invention also provides the application of the oxide-doped indium oxide-based target material described in the above technical solution or the oxide-doped indium oxide-based target material prepared by the preparation method described in the above technical solution in the photovoltaic industry.
[0053] This invention does not impose any special limitations on the application of the oxide-doped indium oxide-based target material in the photovoltaic industry; any application method known in the art can be used.
[0054] The present invention also provides a transparent conductive oxide thin film, which is prepared by sputtering an indium titanium oxide cerium niobium ceramic target.
[0055] The indium titanium cerium niobium ceramic target is the indium titanium cerium niobium ceramic target described in the above technical solution or the indium titanium cerium niobium ceramic target prepared by the preparation method described in the above technical solution.
[0056] In one embodiment, the sputtering coating is a physical vapor deposition sputtering coating; the power of the sputtering coating is 120-200W, specifically 180W in this embodiment; the sputtering gas used for the sputtering coating is argon, and the atmosphere used for the sputtering coating is a mixture of oxygen and hydrogen, wherein the volume ratio of oxygen to hydrogen is 1.5-2:1, specifically 1.8:1 in this embodiment; the thickness of the transparent conductive oxide film is 80-120nm, specifically 100-110nm in this embodiment.
[0057] In one embodiment, the carrier mobility of the transparent conductive oxide thin film is ≥68 cm⁻¹. 2 V -1 S -1 In specific embodiments, the length is 68–78 cm. 2 V -1 S -1 The average transmittance in the 400–1200 nm range is >87%, with a specific range of 87.5–90.3% in the embodiments.
[0058] The present invention does not impose any particular limitation on the application of the transparent conductive oxide film; any application method known in the art may be used.
[0059] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention, but they should not be construed as limiting the scope of protection of the present invention.
[0060] Example 1
[0061] Indium oxide powder, titanium oxide powder, cerium oxide powder, and niobium oxide powder were weighed according to a mass ratio of 97.3:0.9:0.9:0.9 and added to a ball mill jar. Simultaneously, based on the total mass of indium oxide, titanium oxide, cerium oxide, and niobium oxide, 40 wt% deionized water, 0.5 wt% triethanolamine, 1.5 wt% PVA, and 0.1 wt% polyoxypropylene glycerol ether were added. The mixture was then ball-milled in a sand mill at 2400 rpm using 0.3 mm diameter zirconia beads as the milling media for 1.5 hours. The particle size of the solid material in the ball-milled slurry was D. 50 =0.2μm, D 90 =0.5μm; After ball milling, the mixture is spray-dried and granulated at 235℃, and then passed through a 60-mesh sieve to obtain a mixed powder;
[0062] The mixed powder was subjected to cold isostatic pressing at 280 MPa for 30 min to obtain a mixed preform of indium titanium cerium niobium oxide.
[0063] The indium titanium cerium niobium mixed preform was placed in a microwave sintering furnace with a microwave frequency of 2.45 GHz. It was heated to 800°C in air at a rate of 1.5°C / min and held for 2 hours for degreasing. Then, oxygen was introduced at a pressure of 0.1 MPa, and the temperature was further increased to 1200°C at a rate of 1.5°C / min and held for 5 hours for sintering. After natural cooling, indium titanium cerium niobium ceramic target material was obtained.
[0064] Examples 2-7 and Comparative Examples 1-5
[0065] The differences between Examples 2-7 and Comparative Examples 1-5 and Example 1 are that the parameters, components and their contents of the preparation method are different, as shown in Table 1.
[0066] Table 1. Process parameters and component contents of each embodiment and comparative example.
[0067]
[0068] Note: The high-temperature sintering in Comparative Example 5 in Table 1 refers to sintering using a microwave-free sintering furnace.
[0069] Application Example 1
[0070] On a cleaned glass substrate, a TCO thin film was deposited using physical vapor deposition sputtering with the indium titanium oxide cerium niobium ceramic target prepared in Example 1. The deposition power was 180W, the sputtering gas was Ar, and the deposition atmosphere was a H2 / O2 mixed gas with a volume ratio of oxygen and hydrogen of 1.8:1. The film thickness was 100nm, resulting in a transparent conductive oxide thin film (TCO thin film).
[0071] Application Examples 2-7 and Comparative Application Examples 1-5
[0072] The difference from Application Example 1 is that the indium titanium oxide cerium niobium ceramic target prepared in Example 1 was replaced with the targets prepared in Examples 2-7 and Comparative Examples 1-5, respectively.
[0073] Performance testing
[0074] 1. Processing binding:
[0075] The targets prepared in the above embodiments and comparative examples were processed according to the dimensions in the drawings, bound to the titanium tubes, and subjected to ultrasonic testing. No dark cracks were found. Then, subsequent coating tests were carried out.
[0076] 2. Coating test:
[0077] The density of the target material was measured by Archimedes' displacement method.
[0078] The bending strength of the target material was measured using a universal testing machine.
[0079] On the cleaned glass substrate, TCO thin films were deposited by sputtering using the targets prepared in the above embodiments and comparative examples. The deposition power was 180W, the sputtering gas was Ar, the deposition atmosphere was a H2 / O2 mixed gas, and the film thickness was 100mm. The mobility of the film was tested using a Hall effect tester, and the average transmittance of the film in the 400-1200nm wavelength range was tested using an ultraviolet spectrophotometer.
[0080] The performance test results of the targets prepared in each embodiment and comparative example, and the TCO films prepared therefrom, are shown in Table 2.
[0081] Table 2 Performance test results of each embodiment and comparative example
[0082]
[0083]
[0084] As shown in the table above, the indium titanium oxide cerium niobium ceramic target prepared by this invention did not exhibit expansion, deformation, or cracking during the sintering process. Furthermore, it possesses high relative density and high flexural strength, and the TCO thin film prepared using it exhibits high carrier mobility and average light transmittance. Simultaneously, compared to traditional high-temperature sintering technology, high-temperature microwave sintering significantly reduces the sintering time. On one hand, the maximum sintering temperature is reduced from 1500–1600℃ to 1100–1200℃, and the holding time at the maximum temperature is reduced from 35 hours to only 3–5 hours. On the other hand, the entire sintering time is reduced from 240–300 hours for conventional sintering to only 30–50 hours to complete the sintering process.
[0085] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An indium titanium oxide cerium niobium ceramic target, characterized in that, It is composed of the following components: indium oxide, titanium oxide, cerium oxide, and niobium oxide; The mass ratio of indium oxide, titanium oxide, cerium oxide and niobium oxide is 97~99:1~0.4:1~0.4:1~0.
2.
2. The indium titanium oxide cerium niobium ceramic target according to claim 1, characterized in that, The indium titanium oxide cerium niobium ceramic target has a relative density of ≥99% and a bending strength of ≥190MPa.
3. The method for preparing the indium titanium oxide cerium niobium ceramic target as described in claim 1 or 2, characterized in that, Includes the following steps: Indium oxide powder, titanium oxide powder, cerium oxide powder, niobium oxide powder, dispersant, binder, defoamer and water are mixed to form a slurry, which is then ball-milled to obtain the ball-milled slurry. The ball-milled slurry is granulated, and the resulting mixed powder is molded to obtain a mixed preform of indium titanium cerium niobium oxide; The indium titanium cerium niobium mixed preform is sequentially degreased and sintered to obtain the indium titanium cerium niobium ceramic target.
4. The preparation method according to claim 3, characterized in that, The sintering temperature is 1100~1200℃, and the holding time is 3~5h.
5. The preparation method according to claim 3 or 4, characterized in that, The sintering is microwave sintering; the microwave frequency of the microwave sintering is 2.45 GHz.
6. The preparation method according to claim 3, characterized in that, The ball mill rotates at a speed of 1000~2500 rpm; the ball milling time is 1~4 hours.
7. The preparation method according to claim 3, characterized in that, The molding process is cold isostatic pressing; the pressure of the cold isostatic pressing is 150~300MPa, and the holding time is 5~30min.
8. The application of the indium titanium oxide cerium niobium ceramic target as described in claim 1 or 2, or the indium titanium oxide cerium niobium ceramic target prepared by the preparation method described in any one of claims 3 to 7, in the photovoltaic industry.
9. A transparent conductive oxide thin film, characterized in that, The indium titanium oxide cerium niobium ceramic target was sputtered and coated. The indium titanium cerium niobium ceramic target is the indium titanium cerium niobium ceramic target as described in claim 1 or 2, or the indium titanium cerium niobium ceramic target prepared by the preparation method described in any one of claims 3 to 7.
10. The transparent conductive oxide thin film according to claim 9, characterized in that, The sputtering coating is a physical vapor deposition sputtering coating; the power of the sputtering coating is 120~200W.
Citation Information
Patent Citations
Preparation method of TCO film with good electroplating liquid corrosion resistance
CN119465033A
